Brooklyn Tides : The Fall and Rise of a Global Borough - Shepard, Benjamin Heim; Noonan, Mark J. (Urban Studies, 2018)
Brooklyn has all the features of a "global borough": It is a base of immigrant labor and ethnically diverse communities, of social and cultural capital, of global transportation, cultural production, and policy innovation. At once a model of sustainable urbanization and overdevelopment, the question is now: What will become of Global Brooklyn? Tracing the emergence of Brooklyn from village outpost to global borough, Brooklyn Tides investigates the nature and consequences of global forces that have crossed the East River and identifies alternative models for urban development in global capitalism. Benjamin Shepard and Mark Noonan provide a unique ethnographic reading of the literature, social activism, and changing tides impacting this ever-transforming space. Cover and interior images of a rapidly transforming global borough by photographer Caroline Shepard.